Determinants of Dividend Policy: Growth Opportunities, Business Risk and Leverage with Size as Moderation - MF. Christiningrum; Ali Rahman (Ridwan Institute, 2023)
To find out whether investment opportunity set, business risk, and leverage affect dividend policy. To determine whether firm size can strengthen/weaken the effect of the investment opportunity set, business risk, and leverage on dividend policy. In this study, dividend policy is measured by dividend payout ratio (DPR), investment opportunity sets are measured using proxies based on the market-to-book value of equity (MBVE), business risk is calculated using the basic earning power ratio (BEPR) proxy, and leverage (debt to equity ratio) as a ratio that describes how much the company conducts debt policy. The firm size variable used in this study is measured using the natural logarithm of total assets. This research is quantitative application research, this research uses interaction test analysis or better known as moderated regression analysis (MRA). The sample was selected using a purposive random sampling method in companies going public on the Indonesia Stock Exchange in the consumer sector for the period 2017-2021. The results of this study indicate that investment opportunity sets do not affect dividend policy, low business risk has a positive effect on dividend policy, and leverage has a positive effect on dividend policy. Size can moderate of the investment opportunity set and low business risk on dividend policy but size cannot moderate the effect of leverage on dividend policy.